Differential mobilization of blubber fatty acids in lactating Weddell seals : evidence for selective use - K Wheatley; P Nichols; M Hindell; R Harcourt; C Bradshaw (2008)
A major source of energy during lactation in mammals is provided through the mobilization of blubber fatty acids (FAs). We investigated the extent to which FAs were mobilized to support both maternal metabolic requirements and milk production in the Weddell seal and how this was reflected in the FA composition of the pup’s blubber at the end of lactation (EL). FA composition of postpartum female blubber was similar in the 2 yr of study (2002 and 2003) but differed markedly by EL. Pup blubber FAs (at EL) were also different between years and did not match that of the mother’s milk or blubber. Milk FA composition changed during lactation, which may have been a reflection of an increase in pup energy demands at different stages of development. In addition, there was evidence of feeding by some females during lactation, with higher levels of some FAs in the milk than in the blubber. Our results indicate that differential mobilization of FAs occurred in lactating Weddell seals and that this was related to total body lipid stores at postpartum. Furthermore, growing pups did not store FAs unmodified, providing evidence that selective use does occur and also that using FA composition to elucidate dietary sources may be problematic in growing individuals.